Multi-level integrative analysis of Protein?Protein Interaction networks: connecting completeness, depth and robustness. (6th August 2010) - Blayney, Jaine K.; Zheng, Huiru; Wang, Haiying; Azuaje, Francisco
A fully extended Protein?Protein Interaction (PPI) network can consist of upwards of several thousand nodes and edges. To simplify analysis, smaller child samples are often used in substitution of the global network. In this study, the impact of different levels of sampling was evaluated on six PPI networks. Results from the case studies suggest that restricting analysis to the first network level, using metrics such as degree and BC, could lead to misrepresentative results, omitting potentially significant nodes. Fault-tolerance analysis also indicates that key nodes within the second network level, and above, contribute to the stability of the global network.